COVID-19 FAQs in paediatric and congenital cardiology: AEPC position paper. (7th March 2021) - Sendzikaite, Skaiste; Heying, Ruth; Milanesi, Ornella; Hanseus, Katarina; Michel-Behnke, Ina
Abstract: The COVID-19 pandemic has had a huge influence in almost all areas of life, affecting societies, economics, and health care systems worldwide. The paediatric cardiology community is no exception. As the challenging battle with COVID-19 continues, professionals from the Association for the European Paediatric and Congenital Cardiology receive many questions regarding COVID-19 in a Paediatric and Congenital Cardiology setting. The aim of this paper is to present the AEPC position on frequently asked questions based on the most recent scientific data, as well as to frame a discussion on how to take care of our patients during this unprecedented crisis. As the times are changing quickly and information regarding COVID-19 is very dynamic, continuous collection of evidence will help guide constructive decision-making.